Tunable plasmon-induced charge transport and photon absorption of bimetallic Au-Ag nanoparticles on ZnO photoanode for photoelectrochemical enhancement under visible light - Lim, Fang Sheng; Tan, Sin Tee; Zhu, Yuanmin; Chen, Jhih-Wei; Wu, Bao; Yu, Hao; Kim, Jung-Mu; Ginting, Riski Titian Ginting; Lau, Kam Sheng; Chia, Chin Hua; Wu, HengAn; Gu, Meng; et al. (American Chemical Society, 2020)
Noble metal nanostructures have been widely explored as an effective method to increase photon absorption and charge separation in plasmonic photocatalysis. In this study, we integrated two different noble metals, gold (Au) and silver (Ag), into Au/Ag bimetallic nanoparticles (BNPs) via solid-state thermal dewetting to investigate the room-temperature electrical conductivity, visible light absorption, and its effect on photoelectrochemical (PEC) activity. The Au/Ag BNPs give rise to extended visible light absorption range, exhibiting localized surface plasmon resonance (LSPR) effect that lead to strong surface-enhanced Raman spectroscopy. X-ray photoelectron spectroscopy shows binding energy shift in Au/Ag BNPs, suggesting electron transfer from Ag to Au where charge transport behavior can be tailored. Kelvin probe force microscopy and conductive atomic force microscopy displayed a significantly enhanced electrical conduction in Au/Ag BNPs due to the lowered Schottky barrier height. When the Au/Ag BNPs are incorporated onto ZnO semiconductor photoanode, the photoactivity was improved with lower charge transport resistance compared to monometallic and pristine ZnO. This work delivers a general approach to understand the plasmon-induced charge interaction, hence the photochemistry of noble metal BNP/semiconductor photoanode by incorporating a controllable composition ratio, which is capable of exploiting the enhanced electrical conduction and LSPR effect for PEC water splitting.